(untitled) (Architecture Image Studies, 2025)
The cooperative sector in Malaysia plays a significant role in socio-economic development, yet governance challenges persist. This study tests at how organisational culture influences the relationship between governance performance and managerial leadership in Malaysian cooperatives. Based on the Resource-Based Theory (RBT), the study suggests that culture and leadership are key intangible resources that can improve the quality of governance. The board of directors, managers, and cooperative members from a variety of industries provided a total of 400 responses. The study examined the proposed mediating link using Partial Least Squares Structural Equation Modelling (PLS-SEM). Partial Least Squares Structural Equation Modelling (PLS-SEM) was used in the study to test the proposed mediating link. These results challenge traditional assumptions in strategic management literature and underscore the unique governance dynamics in cooperatives, where formal structure, member control, and regulatory compliance may override cultural and leadership influences. These findings suggest that, within Malaysian cooperatives, formal governance structures and regulatory compliance may have a more substantial impact on governance performance than leadership and culture alone. The paper concludes with theoretical and practical implications, suggesting the need for context-sensitive frameworks for cooperative governance.